24 Dealing with delirium: a multi-trust, multi-disciplinary simulation education programme for the management of delirium in elderly care, icu and ed. (17th November 2016) - Burton, K; Saunders, A; Clarke, P; Feely, NM
Abstract : Background: With an ageing population and greater rates of dementia, patients in hospital are at increased risk of delirium. 1 Delirium poses complex challenges because it raises both legal and ethical dilemmas. The Dealing with Delirium Programme was established to address these challenges. Methods: The curriculum comprised four clinical themes: assessment of delirium, management of aggression, post-fall reviews and capacity/deprivation of liberty. For each topic, a structured clinical simulation scenario was designed for doctor and nurse participants, with facilitators taking the roles of a patient and health care assistant. Three courses were run for staff from general medical and elderly care wards. Adapted versions of the programme were produced for Intensive Care (ICU) and the Emergency Department (ED). Participants completed pre- and post-programme Likert scale questionnaires to assess their confidence with complex aspects of delirium management. Participants also recorded qualitative feedback on the impact on their practice. Results: The initial programmes included 16 multi-disciplinary participants. The ICU and ED programmes each involved 6 participants. In every course, confidence increased across all skill areas. Confidence in recognising delirium increased by a mean of 2.5 points on the general medical course, 2.3 points on the ICU course and 1.0 point on the ED course. Confidence in capacity and deprivation of liberty decisions increased by a mean of 3.8, 3.3 and 4.9 points on the general medical, ICU and ED courses respectively. Qualitative feedback highlighted the importance of addressing capacity assessments. Conclusions: We demonstrate that simulation is an effective way to build the confidence of multidisciplinary teams in managing patients with delirium. As the challenges of delirium are growing and often overlooked, such educational techniques are valuable for quality improvement and patient safety. Reference: NICE clinical guideline 103, Delirium: diagnosis, prevention and management; July 2010